2021
DOI: 10.1037/cdp0000350
|View full text |Cite
|
Sign up to set email alerts
|

The correlates of sexual experience and reasons for abstinence among Asian Americans.

Abstract: Objective: This study examines the sexual socialization experiences of Asian American emerging adults by assessing the content and frequency of parent and peer sexual communication and their links to sexual experience and reasons for abstinence. Method: In addition to reports of parent and peer communication on four discourses-abstinence until marriage, gendered sexual roles, acceptance of casual sex, and sex is taboo-154 college students (44% female, M ϭ 19.21 years old) also reported on language use with par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Consistent with previous research on SVSH in college campus environments, our study demonstrated how factors across different socio-ecological levels shaped Asian students; perceptions of and responses to SVSH. These factors included the following: (a) individual-level perceptions of self-blame, guilt, and fear related to SVSH victimization ( Gilligan & Akhtar, 2006 ; Kenny & McEachern, 2000 ; Koo et al, 2012 , 2015 ; Okazaki, 2002 ; (b) interpersonal dynamics with family and friends that were negative or unsupportive ( Kim & Ward, 2007 ; Kim, 2009 ; Liang et al, 2008 ; Malik et al, 2020 ; Morgan et al, 2010 ; Trinh & Kim, 2021 ); (c) complicated and often distrusted institutional procedures encompassing Title IX, campus police, and university administration ( Goldman, 2019 ; Gómez, 2022 ; Monteith et al, 2016 ; Smith & Freyd, 2013 ); and (d) societal norms that perpetuated negative discourse surrounding SVSH ( Brubaker et al, 2017 ; Daigle et al, 2018 ; Holland & Cortina, 2017 ; Postel, 2015 , 2020 ; Scholl et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with previous research on SVSH in college campus environments, our study demonstrated how factors across different socio-ecological levels shaped Asian students; perceptions of and responses to SVSH. These factors included the following: (a) individual-level perceptions of self-blame, guilt, and fear related to SVSH victimization ( Gilligan & Akhtar, 2006 ; Kenny & McEachern, 2000 ; Koo et al, 2012 , 2015 ; Okazaki, 2002 ; (b) interpersonal dynamics with family and friends that were negative or unsupportive ( Kim & Ward, 2007 ; Kim, 2009 ; Liang et al, 2008 ; Malik et al, 2020 ; Morgan et al, 2010 ; Trinh & Kim, 2021 ); (c) complicated and often distrusted institutional procedures encompassing Title IX, campus police, and university administration ( Goldman, 2019 ; Gómez, 2022 ; Monteith et al, 2016 ; Smith & Freyd, 2013 ); and (d) societal norms that perpetuated negative discourse surrounding SVSH ( Brubaker et al, 2017 ; Daigle et al, 2018 ; Holland & Cortina, 2017 ; Postel, 2015 , 2020 ; Scholl et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, studies have shown that parents convey messages like abstinence, gendered sex roles, and sex as taboo in Asian households. Such restrictive messages around sexuality reinforce conservative and gender-stereotypical attitudes ( Kim & Ward, 2007 ; Kim, 2009 ; Liang et al, 2008 ; Malik et al, 2020 ; Morgan et al, 2010 ; Trinh & Kim, 2021 ). In a survey conducted with East and Southeast Asian college female students, respondents reported that their parents were the least common source of their sex education ( Lee et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the heterogenicity among Asian and Pacific Islanders (APIs), and APIs being the fastest-growing racial/ethnic group in the United States, researchers often have overlooked APIs, as clinicians perceive this population as having minimal health concerns, partly due to the “model minority” myth ( Shih et al, 2019 ; Trieu et al, 2013 ). When studies have included APIs, they often have involved a small, limited sample size and often aggregate research data to represent the API umbrella ( Ansari-Thomas et al, 2020 ; Trinh & Kim, 2021 ). Combining data gives a false sense of reassurance that API subgroups have all done well uniformly.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Further, Black adolescents have demonstrated greater likelihood of having at least three‐lifetime sexual partners compared to White adolescents, which is associated with greater risks of sexually transmissible infection (E. Williams et al, 2018). Unfortunately, a relative paucity of sexual health research among Asian and Multiracial youth precludes comparisons among these two groups (Landor & Halpern, 2016; Trinh & Kim, 2021). The present study sought to identify environmental correlates of the disparities in adolescent health risk behaviors across racial groups by investigating the potential direct roles of neighborhood contexts.…”
Section: Introductionmentioning
confidence: 99%